Molecular characterization of Ctenotaenia marmotae (Frölich, 1802) Railliet, 1893 (Cyclophyllidea: Anoplocephalidae) parasitizing rodents of the genus Marmota and Spermophilus from Eurasia - Krivopalov, Anton V.; Abramov, Sergey A.; Akimova, Lyudmila; Barkhatova, Alina; Gromov, Anton; Konyaev, Sergey; Lopatina, Natalia; Sidorovich, Anna; Vlasov, Egor; Vlasenko, Pavel G.; Zinchenko, Vadim K. (Diversity)
Cestodes Ctenotaenia marmotae are a widespread parasite of Eurasian ground squirrels. Being the only valid species of its genus, it has been recorded in ten host species from the genera Marmota and Spermophilus. Its definitive hosts live in similar ecological conditions and their area covers a wide geographical territory. Therefore, it remained unclear whether C. marmotae is a single species and how high the level of its genetic variability is. The present study analyzed the variability of two mitochondrial cestode genes from four host species from geographically distant localities. Phylogenetic analysis revealed that the newly obtained sequences form a species-level clade with already known sequences from the GenBank. Small genetic distances between the studied sequences indicate low intraspecific genetic variability within the C. marmotae, which may be a consequence of rapid expansion of the cestodes in ground squirrel species inhabiting the flat and mountain steppe landscapes in the past.